RANKL regulates male reproductive function - Jensen Martin Blomberg; Andreassen Christine Hjorth; Jørgensen Anne; Nielsen John Erik; Mortensen Li Juel; Boisen Ida Marie; Schwarz Peter; Toppari Jorma; Baron Roland; Lanske Beate; Juul Anders (NATURE RESEARCH, 2022)
Infertile men have few treatment options. Here, we demonstrate that the transmembrane receptor activator of NF-kB ligand (RANKL) signaling system is active in mouse and human testis. RANKL is highly expressed in Sertoli cells and signals through RANK, expressed in most germ cells, whereas the RANKL-inhibitor osteoprotegerin (OPG) is expressed in germ and peritubular cells. OPG treatment increases wild-type mouse sperm counts, and mice with global or Sertoli-specific genetic suppression of Rankl have increased male fertility and sperm counts. Moreover, RANKL levels in seminal fluid are high and distinguishes normal from infertile men with higher specificity than total sperm count. In infertile men, one dose of Denosumab decreases RANKL seminal fluid concentration and increases serum Inhibin-B and anti-Mullerian-hormone levels, but semen quality only in a subgroup. This translational study suggests that RANKL is a regulator of male reproductive function, however, predictive biomarkers for treatment-outcome requires further investigation in placebo-controlled studies. There are few treatments for male infertility. Here, the authors show that the receptor activator of NF-kappa B ligand (RANKL) signalling pathway has important functions in sperm production and maturation, improves fertility in male mice and shows potential as a male infertility target.